2014
DOI: 10.1155/2014/790615
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Excitation Frequency on the Sensitivity in Metal Debris Detection with Inductor Sensor

Abstract: The nonferromagnetic debris is easier to be detected as the excitation frequency increases; however, the sensitivity of ferromagnetic metal debris decreases as the excitation frequency increases. This paper is aimed at finding a range of excitation frequency that fit both ferromagnetic metal debris detection and nonferromagnetic metal debris detection. The equivalent circuit of the metal debris detection system with microinductor sensor is analyzed in this paper. The formulae of relationship between the sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…2. The detection model adopts a symmetrical reverse double-coil structure and uses a magnetically inert material that is not affected by magnetic field energy as the skeleton of the coil [30]. It includes two sets of reverse winding excitation coils and one set of induction coils.…”
Section: Online Symmetric Magnetic Excitation Monitoring Sensor For Metal Wear Debrismentioning
confidence: 99%
“…2. The detection model adopts a symmetrical reverse double-coil structure and uses a magnetically inert material that is not affected by magnetic field energy as the skeleton of the coil [30]. It includes two sets of reverse winding excitation coils and one set of induction coils.…”
Section: Online Symmetric Magnetic Excitation Monitoring Sensor For Metal Wear Debrismentioning
confidence: 99%
“…Additionally, results obtained by the solenoid coil sensor [ 24 ] indicated that its sensitivity to ferrous and non-ferrous metal debris in the inner diameter of the pipe, which was approximate 43 mm, could be achieved with values of 70 µm (diameter) and 165 µm, respectively. Liu et al [ 25 ] investigated the relationship between the excitation frequency of the microinductor sensors and the rate of change of the sensor inductance. The sensitivity of ferrous metal debris decreased with the increasing excitation frequency, while the sensitivity of non-ferrous metal debris increased with the excitation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Wear debris flowing along lubrication systems can potentially rub against the surface of friction pairs and clog flow channels, resulting in severe damage to machines, especially to sensitive and critical parts. According to the research, abrasion and lubrication failures occupy approximately 80% of mechanical faults [1,2]. Thus, effective condition monitoring technologies are necessary for the timely prevention of machinery faults and unwanted production delays.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the inductance and the resistance methods, the planar coil with 20 turns can detect 55 µm iron particles and 115 µm copper particles. Liu analyzed the relationship between sensitivity and excitation frequency and concluded that high sensitivity can be obtained if suitable excitation frequency is chosen [1]. Ren proposed an effective signal processing system with an unbalance compensation module to reduce the effects on sensitivity due to coil asymmetry [19].…”
Section: Introductionmentioning
confidence: 99%